The unilateral biportal endoscopy journey: proposing a 10-tier difficulty progression framework for unilateral biportal endoscopy - Xavier Augusto Santander Espinoza; Elsa González Pérez; Dae-Jung Choi (Asian Spine Journal)
Unilateral biportal endoscopy (UBE) has revolutionized minimally invasive spinal surgery, offering enhanced visualization and reduced recovery times. However, the steep learning curve and technical complexity require a structured training framework. This narrative review proposes a 10-tier difficulty progression framework for UBE designed to guide novice surgeons through incremental skill acquisition. Each tier corresponds to specific procedures with escalating challenges spanning lumbar, cervical, and thoracic pathologies. The proposed framework begins with foundational lumbar procedures, such as ipsilateral recess decompression and discectomy, and advances to more intricate techniques, such as transforaminal lumbar interbody fusion. Transitioning to the cervical and thoracic regions requires mastery of earlier tiers, emphasizing precision in handling delicate anatomical structures. These challenges include achieving proficiency in mobilizing nerve roots, minimizing spinal cord manipulation, and mastering advanced decompression techniques. Evidence from learning curve analyses, including cumulative sum methodologies, underscores the importance of tailored training to reduce complications and optimize outcomes. By standardizing the progression of UBE procedures, this framework aims to enhance surgical safety, improve patient outcomes, and facilitate their widespread adoption. Future research should focus on validating this framework by using clinical trials, training feedback, and long-term patient data. Ultimately, this 10-tiered approach provides a roadmap for mastering UBE, addressing the growing demand for minimally invasive spinal surgery with precision and confidence.